2000
DOI: 10.4314/jsda.v15i1.23854
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Conflict and Democracy in Nigeria: The Marginalisation Question

Abstract: The African e-Journals Project has digitized full text of articles of eleven social science and humanities journals. This item is from the digital archive maintained by Michigan State University Library.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 10 publications
(2 reference statements)
1
26
0
Order By: Relevance
“…However, having more female students on a higher socioeconomic scale in this study than males is a new development in Nigeria and indeed Africa. Previous studies indicated that due to patriarchal African culture, males are more valued than females and females are generally viewed as subordinates to males, [67,18] consequently, the training of boys in school is given more priority, both financially and morally, than girls in the past.…”
Section: Socio-economic Status and Social Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…However, having more female students on a higher socioeconomic scale in this study than males is a new development in Nigeria and indeed Africa. Previous studies indicated that due to patriarchal African culture, males are more valued than females and females are generally viewed as subordinates to males, [67,18] consequently, the training of boys in school is given more priority, both financially and morally, than girls in the past.…”
Section: Socio-economic Status and Social Supportmentioning
confidence: 99%
“…The study also indicated a significant positive social support for the students. This is one of the cultural characteristics of African people to live and participate in community life system, [67]. African cultural norms encourages community participation, and extended family system, which can be achieved through blood relationship or belonging to an organized religion, social organization, or trade unions which provide collective support, both financial and emotional supportto each other.…”
Section: Socio-economic Status and Social Supportmentioning
confidence: 99%
“…One key argument that arises however is how long Africans and African voices such as Mafeje (1971), Nnoli (1978) and Anugwom (2000) will persist in levelling the ethnic problem that has so hindered development in Africa at the doorstep of the colonial masters? Decolonisation in Africa commenced in the 50's and terminated in the 80's with countries like Zimbabwe becoming independent.…”
Section: Ethnicity and National Developmentmentioning
confidence: 99%
“…Ethnic crisis can therefore be argued to have contributed to Africa's current state of economic decadence and under development (Brown 1995, Madiebo 1980, Osaghae 1998, Collier 2008). In the case of Nigeria, it is still quite common for the blame of ethnicity and its resultant effect on national development to be levelled against the colonial government and the political structures inherited from it upon departure in 1960 (Nnoli 1978, Anugwom 2000. Brown (1995) across their various colonies applied the 'divide and rule' system of government to achieve firm control of their colonies while the French colonial government applied the system of total assimilation to control their colonies.…”
Section: Ethnicity and National Developmentmentioning
confidence: 99%
See 1 more Smart Citation